Successful desensitization to colistin in a Peruvian patient with cystic fibrosis - Veramendi-Espinoza, Liz (2023)
Introduction: Pharmacological desensitization induces a temporary hyposensitivity to the causative drug in patients with Immunoglobulin E-mediated drug reactions. Case of report: We present the case of a patient with respiratory exacerbation of cystic fibrosis who presented immediate hypersensitivity to colistin, an essential antibiotic for its treatment—both due to the sensitivity of the microorganism and the lack of availability of other drugs. The procedure was successfully performed in the Intensive Care Unit, and the patient completed the treatment schedule. Conclusion: Currently, the patient is undergoing specific treatment for his underlying disease and has not presented any new episodes of exacerbation or pneumonia.